Age and competition level on injuries in female ice hockey - Keightley, M.; Reed, N.; Green, S.; Taha, T. (International Journal of Sports Medicine, 2013)
The objective of this study was to describe the number, types and locations of known injuries occurring across different age categories and levels of competition in female ice hockey within the Ontario Women's Hockey Association from 2004/05 to 2007/08. We further examined under which aforementioned factors and combination of factors an unusually high or low number of injuries was recorded. Secondary analysis of anonymized injury data was conducted. The most common known injury type was strain/sprain, followed by concussion while the most frequent injury location was head/face/mouth. Analysis of deviance indicated that a significantly higher than expected number of sprain/strain, concussion and laceration injuries were recorded compared to all other injury types. In addition, there were a higher number of injuries recorded at the AA level compared to all other levels of competition. Finally, the age categories of Peewee, Midget and Intermediate within the AA level of competition, as well as Senior/Adult within the Houseleague level of competition also recorded a significantly higher number of injuries compared to other combinations of descriptive factors. Further research with female youth is needed to better understand the high number of injuries, including concussions, reported overall.